Fluorescent ceramic, preparation method thereof and light-emitting device
By introducing a cladding layer and a variety of fluorescent particle phases into the fluorescent ceramics, physical isolation and independent luminescence of the ceramic phases are achieved, and the thermal quenching problem of fluorescent ceramics under high-power laser excitation is solved, the thermal conductivity and thermal stability of the ceramics are improved, and the efficient and wide-spectrum fluorescent emission and effective regulation of white light sources are achieved.
Patent Information
- Application Number
- CN202311725726.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-14
- Publication Date
- 2025-06-24
AI Technical Summary
Existing fluorescent ceramics are prone to thermal quenching problems under high-power laser excitation, and their thermal conductivity and thermal stability are insufficient, making it difficult to meet the needs of high-power laser white light illumination light sources.
A fluorescent ceramic is used, which includes a fluorescent matrix, a first fluorescent particle and a second fluorescent particle, which is respectively filled in the fluorescent matrix and covers its outer surface by a cladding layer to achieve physical isolation and independent luminescence of different ceramic phases. At the same time, by adjusting the proportion of the ceramic phase, adjusting the emission spectral composition, and improving the density and thermal conductivity of the ceramic.
It realizes high-efficiency wide-spectral fluorescence emission, improves the thermal conductivity and thermal stability of the ceramic, can withstand high-power laser excitation, and effectively regulates the color rendering index and color temperature of the white light source.
Smart Images

Figure CN120192157A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of luminescence technology, and particularly relates to a fluorescent ceramic, a preparation method thereof, and a light-emitting device. Background Art
[0002] In the lighting technology of realizing white light sources by laser-excited fluorescent materials, due to its advantages such as high brightness, high luminous flux, and low energy consumption, it has been widely used in optoelectronic technologies such as automotive headlights, projection displays, and space navigation lighting. However, currently, the commercial encapsulation materials for phosphors are epoxy resins or silicones, which have low heat resistance and thermal conductivity (0.1 - 0.4 W·m-1·K-1). This method of adding organic glue to the phosphor will be difficult to overcome the problem of thermal quenching, thereby affecting the performance of white LD devices.
[0003] In the prior art, for the purpose of solving the problem of thermal quenching, a solution of using inorganic materials as fluorescence conversion materials has been proposed. Among them, the thermally robust Ce 3+ -doped fluorescent ceramic materials have excellent optical and mechanical properties, and the preparation process is flexible and controllable, which is the most promising new type of inorganic fluorescent material. Nevertheless, the white LD devices with the traditional YAG:Ce 3+ ceramic light converter structure still have problems of low color rendering index (CRI: 60) and highly correlated color temperature (CCT: 5000K).
[0004] Since the smaller the spot size of the laser, the greater the laser power per unit area that the fluorescent ceramic bears. After being able to withstand the thermal shock of the fluorescent ceramic, due to the laser excitation here, a part of the light is converted into heat and will continuously accumulate in the ceramic. In the process of achieving stable and efficient luminescence, the fluorescent ceramic needs to be able to quickly conduct out the generated heat. Therefore, not only excellent thermal stability of luminescence is required, but also the thermal conductivity of the ceramic should be increased as much as possible. Currently, a single fluorescent ceramic system is difficult to withstand high-power density laser excitation. Limited by the requirements of the volume size of LD light source devices, improving the power density threshold of fluorescent ceramics still requires improving the thermal conductivity and thermal stability of the fluorescent ceramics themselves to meet the R & D and production requirements of high-power laser white light illumination sources. Summary of the Invention
[0005] The purpose of the present application is to provide a fluorescent ceramic, a preparation method thereof, and a light-emitting device to improve the above technical problems.
[0006] In a first aspect, an embodiment of the present application provides a fluorescent ceramic, including:
[0007] A fluorescent matrix;
[0008] A first fluorescent particle filled in the fluorescent matrix;
[0009] A second fluorescent particle, filled within a fluorescent matrix; and
[0010] A coating layer, coating the outer surface of the first fluorescent particle and the outer surface of the second fluorescent particle;
[0011] Wherein, the coating layer separates the fluorescent matrix, the first fluorescent particle and the second fluorescent particle from each other.
[0012] In some embodiments, the fluorescent matrix, the first fluorescent particle and the second fluorescent particle respectively generate stimulated emission light in different wavelength bands when being excited.
[0013] In some embodiments, the wavelength bands of the stimulated emission light generated when the fluorescent matrix, the first fluorescent particle and the second fluorescent particle are excited are independently 490 nm - 515 nm or 515 nm - 530 nm or 535 nm - 560 nm.
[0014] In some embodiments, the fluorescent matrix is a Ce 3+ doped garnet structure.
[0015] In some embodiments, the coating layer comprises one or more of SiO2 or MgO or Al2O3 or YAG or LuAG.
[0016] In some embodiments, the proportion of the coating layer in the total volume of the fluorescent ceramic is 2% - 10%.
[0017] In some embodiments, the thickness of the coating layer is 50 nm - 200 nm.
[0018] In some embodiments, the total volume of the first fluorescent particle and the second fluorescent particle accounts for 10% - 80% of the total volume of the fluorescent ceramic.
[0019] In a second aspect, the embodiments of the present application further provide a preparation method of the above-mentioned fluorescent ceramic, including respectively coating a coating layer on the surface of the first fluorescent particle and the surface of the second fluorescent particle, selecting a fluorescent matrix, mixing with the first fluorescent particle and the second fluorescent particle after coating the coating layer, and obtaining the product after sintering.
[0020] In some embodiments, respectively coating a coating layer on the surface of the first fluorescent particle and the surface of the second fluorescent particle includes:
[0021] Selecting the first fluorescent particle, adding a coating layer material, a dispersant, a binder and absolute ethanol, mixing evenly, grinding and drying, and calcining at 800 °C - 1000 °C for at least 2 h to obtain the first fluorescent particle coated with the coating layer;
[0022] Select the second fluorescent particles, add the coating material, dispersant, binder and absolute ethanol. After mixing evenly, grind and dry, and calcine at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particles coated with the coating layer.
[0023] In some embodiments, the sintering is carried out under the following conditions: under vacuum or protective atmosphere, hot pressing or spark plasma sintering or isostatic pressing sintering is carried out, the sintering temperature is 1500 °C to 1700 °C, the sintering pressure is 30 MPa to 100 MPa, and the heat preservation is 10 min - 10 h.
[0024] In some embodiments, the method further includes a step of annealing treatment after sintering. The annealing treatment is carried out in the following manner: carried out in air or oxygen atmosphere, the annealing temperature is 1000 °C to 1300 °C, and the heat preservation time is 2 h to 100 h.
[0025] In a third aspect, the embodiments of the present application further provide a light-emitting device, including an excitation light source and the fluorescent ceramic of any one of the above, and the excitation light source can emit excitation light for exciting the fluorescent ceramic to emit stimulated light.
[0026] For the fluorescent ceramic, its preparation method and the light-emitting device provided by the present application, on the one hand, can achieve physical isolation of different luminescent ceramic phases, realize independent luminescence of different ceramic phases, and obtain high-efficiency broadband fluorescence emission; on the other hand, the coating layer effectively reduces the pores around the first fluorescent particles and the second fluorescent particles, improves the density of the ceramic, can enhance the thermal conductivity of the fluorescent ceramic, and can withstand high-power laser excitation; further, by changing the ratio of the three ceramic phases, the emission spectrum components of the fluorescent ceramic can be adjusted, and the color rendering index and color temperature of the white light source excited by high-power blue laser can be effectively regulated.
[0027] These aspects or other aspects of the present application will be more clearly understood in the following description of the embodiments. Description of the Drawings
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the following drawings are only some embodiments of the present application. For those skilled in the art, without creative efforts, other drawings can also be obtained according to these drawings.
[0029] Figure 1 It is a schematic structural diagram of a fluorescent ceramic provided by an embodiment of the present application.
[0030] Figure 2 It is a schematic structural diagram of a light-emitting device provided in Embodiment 5 of the present application. Detailed Embodiments
[0031] Next, the technical solutions in the embodiments of the present application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without making creative efforts belong to the scope of protection of the present application.
[0032] At present, the fluorescent module of a laser illumination source generally only contains one kind of luminescent ceramic phase, such as YAG:Ce 3+ or LuAG:Ce 3+ , although it can achieve a relatively high lumen efficiency, its spectral emission range is limited, and it is difficult to achieve diversified white light illumination with a high color rendering index and a low color temperature. Moreover, as the types and quantities of doped luminescent ions increase, the luminescence efficiency deteriorates continuously, resulting in easy optical saturation in fluorescence conversion and difficulty in meeting the requirements of high-power laser illumination sources. Therefore, the current technological development trend is to innovate and develop new matrix fluorescent ceramic materials, establish physical isolation between different fluorescent ceramic phases to ensure that different fluorescent ceramic phases can emit light independently and efficiently, and at the same time use structural design and process control to achieve the coordinated unity of the luminescence spectrum combination and high thermal conductivity of the fluorescent ceramic, so as to realize the preparation of fluorescent ceramic materials with high efficiency, high thermal conductivity, and full spectrum. At present, general fluorescent ceramics mainly include two types. One is a two-phase fluorescent ceramic prepared by sintering commercial fluorescent powder YAG:Ce 3+ together with alumina, which only contains YAG:Ce 3+ one kind of luminescent ceramic phase; the other is a single-phase ceramic using YAG:Ce 3+ or LuAG:Ce 3+ or GAGG:Ce 3+ . For the first type of two-phase fluorescent ceramic, since the alumina phase has a relatively high thermal conductivity and mechanical strength, it mainly plays a role in heat dissipation and skeleton and does not participate in the luminescence process. However, the alumina phase is the main matrix material, which occupies most of the volume of the ceramic and is not conducive to the effective absorption of blue laser by the fluorescent powder, thus affecting its conversion efficiency for blue light; for the second type of pure-phase fluorescent ceramic form, taking YAG:Ce 3+ as an example, in order to obtain a relatively high blue light conversion efficiency, the YAG:Ce 3+ ceramic has a porous structure with a relatively low density. The porous structure makes the thermal conductivity of the ceramic relatively low and the mechanical strength poor, which is not conducive to subsequent processing; moreover, the pure-phase porous YAG:Ce 3+For ceramics, it is difficult to precisely control the pore distribution and size, and the batch stability of ceramic preparation is poor, which is not suitable for mass production. Generally speaking, the more pores in the fluorescent ceramic, the more beneficial it is to the fluorescence extraction efficiency of the ceramic. However, if there are too many pores in the fluorescent ceramic, on the one hand, it affects the heat dissipation of the ceramic, and on the other hand, the strength performance of the ceramic decreases, making it difficult to meet the actual application requirements.
[0033] There is an urgent need to design an LD lighting device that can achieve wide-spectrum lighting, high color rendering index, low color temperature, high efficiency, and high stability. Based on this, the inventors of the present application have proposed a fluorescent ceramic, its preparation method, and a light-emitting device, in order to improve the above technical problems, which will be specifically described below with reference to the accompanying drawings.
[0034] Referring to Figure 1 , the present application provides a fluorescent ceramic 10, which includes a fluorescent matrix 100, a first fluorescent particle 200, a second fluorescent particle 300, and a coating layer 400. The first fluorescent particle 200 is filled in the fluorescent matrix 100; the second fluorescent particle 300 is filled in the fluorescent matrix 100; the coating layer 400 coats the outer surface of the first fluorescent particle 200 and the outer surface of the second fluorescent particle 300; wherein, the coating layer 400 separates the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 from each other to form a non-contact fluorescent matrix phase, a first fluorescent phase, and a second fluorescent phase. By setting the coating layer 400, the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 are physically separated into different fluorescent ceramic phases, realizing independent light emission of different ceramic phases, avoiding mutual absorption of light emission of different fluorescent ceramic phases, losing the original emission color, and obtaining high-efficiency wide-spectrum fluorescence emission. At the same time, during the formation of the coating layer 400, it will also occupy the pore positions remaining between different fluorescent ceramic phases, effectively reducing the pores around the first fluorescent particle 200 and the second fluorescent particle 300, improving the density of the ceramic, being able to enhance the thermal conductivity of the fluorescent ceramic 10, and being able to withstand high-power laser excitation; further, by adjusting the proportions of the three different ceramic phases, the emission spectrum components of the fluorescent ceramic 10 can be effectively adjusted, and the color rendering index and color temperature of the white light source excited by high-power blue laser can be effectively regulated.
[0035] It should be noted that in some embodiments of the present application, it is desirable that the coating layer 400 completely coats the outer surface of the first fluorescent particle 200, and it is also desirable that the coating layer 400 completely coats the outer surface of the second fluorescent particle 300. By "100% coating" it means that the entire outer surface of the fluorescent particle is coated so that there is no possibility of direct contact between the fluorescent particle and the outside. However, during the preparation process, due to insufficient interaction between the coating layer and the outer surfaces of the first and second fluorescent particles, a small part of the coating layer peels off, resulting in the situation that part of the coating layer 400 does not completely coat the outer surface of the first fluorescent particle 200 and part of the coating layer 400 does not completely coat the outer surface of the second fluorescent particle 300. Nevertheless, the inventors have found that even if the outer surface of the fluorescent particle is not completely coated by 100%, the absorption of light of different wavelengths by each other and the resulting significant loss are sufficiently reduced compared to the case where the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 are in direct contact with each other. Among them, the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 can all generate stimulated light (fluorescence) under the excitation of the excitation light. In this way, the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 can generate three-phase fluorescence. By reasonably selecting the materials of the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300, various luminescence combinations can be achieved. In one embodiment, the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 can generate stimulated light of different wavelength bands when excited by the excitation light. In this way, the emission spectrum of the entire fluorescent ceramic 10 can be made wider to adapt to different usage scenarios.
[0036] Specifically, in a more specific embodiment, the wavelength bands of the stimulated light generated when the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 are excited are independently 490 nm - 515 nm (cyan light) or 515 nm - 530 nm (green light) or 535 nm - 560 nm (orange-yellow light). That is, each of the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300 can be configured to generate light with a wavelength in the range of 490 nm - 515 nm (cyan light) or 515 nm - 530 nm (green light) or 535 nm - 560 nm (orange-yellow light). In this way, various luminescence combinations can be formed among the fluorescent matrix 100, the first fluorescent particle 200, and the second fluorescent particle 300. For example, the luminescence color combinations of the first fluorescent particle 200 and the second fluorescent particle 300 are cyan light + green light, cyan light + orange-yellow light, and green light + orange-yellow light respectively. Correspondingly, the luminescence of the fluorescent matrix 100 is orange-yellow light, green light, and cyan light. That is, in some embodiments of the present application, the fluorescent ceramic always has the luminescence color combination: cyan light + green light + orange-yellow light.
[0037] Specifically, the fluorescent matrix 100 can be selected as Ce 3+ doped garnet structure, such as YAG:Ce 3+ , LuAGG:Ce 3 + , LuAG:Ce 3+ , GAGG:Ce 3+ etc., and this embodiment does not make specific limitations thereto. Ce 3+ doped garnet structure has the characteristics of stable chemical properties, good mechanical properties, good thermal stability, can be perfectly matched with blue LED / LD chips, has a simple manufacturing process and low production cost during preparation, can be mass-produced, has an easily controllable doping concentration, has a high thermal conductivity, and has good thermal quenching performance.
[0038] The particle sizes of the first fluorescent particles 200 and the second fluorescent particles 300 can be in the range of 0.2 μm to 30 μm, preferably 5 μm to 20 μm, and the particle shape is spherical or polyhedral, and this embodiment does not make limitations thereto. Among them, according to the light emission requirements, the addition amounts of the first fluorescent particles 200 and the second fluorescent particles 300 can be adjusted. In one embodiment, the total volume of the first fluorescent particles 200 and the second fluorescent particles 300 can account for 10%-80% of the total volume of the fluorescent ceramic 10. For example, the total volume of the first fluorescent particles 200 and the second fluorescent particles 300 can account for 10%-50% or 50%-80% of the total volume of the fluorescent ceramic 10. More preferably, the total volume of the first fluorescent particles 200 and the second fluorescent particles 300 can account for 20%-60% of the total volume of the fluorescent ceramic 10. Among them, the volume contents of the first fluorescent particles 200 and the second fluorescent particles 300 can be the same or different, and no limitations are made here.
[0039] The first fluorescent particles 200 and the second fluorescent particles 300 can also adopt Ce 3+ doped garnet structure, such as YAG:Ce 3+ , LuAGG:Ce 3+ , LuAG:Ce 3+ , GAGG:Ce 3+ etc., and this embodiment does not make specific limitations thereto.
[0040] The coating layer 400 coats the outer surfaces of the first fluorescent particles 200 and the second fluorescent particles 300, such that the first fluorescent particles 200 and the second fluorescent particles 300 are respectively separated from the fluorescent matrix 100 as a whole, that is, the first fluorescent particles 200, the second fluorescent particles 300 and the fluorescent matrix 100 cannot directly contact each other. Such a setting method is conducive to the discharge of air holes during the preparation of the fluorescent ceramic 10, and a three-phase fluorescent ceramic 10 with a dense microstructure is obtained. It should be noted that in some embodiments of the present application, different first fluorescent particles 200 coated by the coating layer 400 are also physically separated from each other; different second fluorescent particles 300 coated by the coating layer 400 are also physically separated from each other.
[0041] The coating layer 400 may include one or more of SiO2, MgO, Al2O3, YAG, or LuAG, which is not limited herein. If the thickness of the coating layer 400 is too large, the luminescence of the fluorescent ceramic will be blocked by the coating layer 400, thereby weakening the luminescence brightness of the fluorescent ceramic 10; while if the thickness of the coating layer 400 is too small, the situation of incomplete coating may occur, such that different fluorescent ceramic phases are in contact with each other, resulting in the luminescence of the different mutually contacting fluorescent ceramic phases being absorbed by each other, and the original luminescence color is lost. Therefore, preferably, the thickness of the coating layer 400 may be 50 nm - 200 nm. Of course, it can be understood that in some other embodiments, the thickness of the coating layer 400 may also be other values.
[0042] Among them, the proportion of the coating layer 400 in the total volume of the fluorescent ceramic 10 may be 2% - 10%. Within this volume ratio range, it can be ensured that the first fluorescent particles 200 and the second fluorescent particles 300 can be coated by the coating layer 400 with a uniform and appropriate thickness. In addition, since the coating layer 400 is a non-luminescent material, it should not have too high a proportion in the total volume of the fluorescent ceramic 10 to avoid reducing the overall luminescence efficiency. Since the coating layer can occupy the pores between other three-phase fluorescent ceramic phases and reduce the porosity inside the whole fluorescent ceramic 10, the volume ratio of the coating layer cannot be too small to avoid the porosity reduction being not obvious and thus the thermal conductivity not being significantly improved. In addition, the volume ratio of the coating layer is related to the sum of the volumes of the first fluorescent particles 200 and the second fluorescent particles 300 to be coated. If the volume ratio of the coating layer is too small, the first fluorescent particles 200 and the second fluorescent particles 300 will not be completely coated, and there will be physical contact between the fluorescent matrix, the first fluorescent particles 200 and the second fluorescent particles 300, resulting in the mutual absorption of different emission bands. Of course, it can be understood that in some other embodiments, the volume ratio of the coating layer 400 may also be other values.
[0043] It is understandable that when the coating layer 400 coats the outer surfaces of the first fluorescent particles 200 and the second fluorescent particles 300 respectively, the coating thickness can be uniform everywhere or non-uniform, and no limitation is imposed thereon.
[0044] The above-mentioned fluorescent ceramic 10 can be prepared in the following manner:
[0045] Coating layers 400 are respectively wrapped on the surfaces of the first fluorescent particles 200 and the second fluorescent particles 300. Specifically, it can be carried out in the following manner:
[0046] Select the first fluorescent particles 200 according to the metering ratio of the first fluorescent particles 200 and the coating layer 400. After weighing the coating layer 400 material and adding it, then adding appropriate amounts of dispersant, binder and absolute ethanol, and mixing evenly, grinding is carried out. The grinding method can be ball milling, which is not limited herein. After grinding, the system is dried. During this process, the coating layer 400 material coats on the surface of the first fluorescent particles 200. After drying, sieving is carried out. The sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the first fluorescent particles 200 coated with the coating layer 400.
[0047] Select the second fluorescent particles 300 according to the metering ratio of the second fluorescent particles 300 and the coating layer 400. After weighing the coating layer 400 material and adding it, then adding appropriate amounts of dispersant, binder and absolute ethanol, and mixing evenly, grinding is carried out. The grinding method can be ball milling. The binder is PVB and its content is 2-5%. The dispersant is at least one of PEG, CTAB, and SDS, which is not limited herein. After grinding, the system is dried. During this process, the coating layer 400 material coats on the surface of the second fluorescent particles 300. After drying, sieving is carried out. The sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particles 300 coated with the coating layer 400.
[0048] Prepare the fluorescent matrix 100. When preparing, weigh the raw materials according to the ratio of the selected fluorescent matrix 100 material. For example, when the fluorescent matrix 100 is YAG:Ce 3+ , weigh Y3Al5O 12 :xCe 3+ in proportion. When the fluorescent matrix 100 is LuAGG:Ce 3+ , weigh Lu3(Al,Ga)5O 12 :xCe 3+ in proportion. When the fluorescent matrix 100 is LuAG:Ce 3+ , weigh Lu3Al5O 12 :xCe 3+ in proportion. When the fluorescent matrix 100 is GAGG:Ce3+ When, proportionally weigh Gd3(Al,Ga)5O 12 :xCe 3+ . Wherein, x is the molar percentage of Ce substituting rare earth elements such as Y, Lu, Gd, etc., and x = 0.01% - 2%.
[0049] After weighing the raw materials, mix and grind the raw materials. The grinding can be carried out by ball milling. During the mixing process, appropriate sintering aids and dispersants are added. After grinding, dry the system, and after drying, sieve it. The sieved powdery material is calcined at 700°C - 900°C for at least 2 h to obtain the fluorescent matrix 100.
[0050] Weigh the fluorescent matrix 100 prepared above, and mix it with the first fluorescent particles 200 coated with the coating layer 400 and the second fluorescent particles 300 coated with the coating layer 400 prepared above according to a predetermined volume ratio. After mixing, it can be sieved again and set aside.
[0051] Under vacuum or protective atmosphere, hot press or spark plasma sintering or isostatic pressing sintering is carried out on the mixed fluorescent matrix 100, the first fluorescent particles 200 coated with the coating layer 400, and the second fluorescent particles 300 coated with the coating layer 400. The sintering temperature is 1500°C - 1700°C, the sintering pressure is 30 MPa - 100 MPa, and keep the temperature for 10 min - 10 h to obtain the fluorescent ceramic 10. After sintering is completed, annealing treatment can also be carried out on the obtained fluorescent ceramic 10. Specifically, the annealing treatment can be carried out in air or oxygen atmosphere, the annealing temperature is 1000°C - 1300°C, and the holding time is 2 h - 100 h. Through the annealing treatment, the internal stress inside the fluorescent ceramic 10 can be eliminated, and the subsequent occurrence of cracks or cracking in the fluorescent ceramic 10 can be avoided.
[0052] The present application will be further described below in conjunction with specific embodiments.
[0053] Example 1
[0054] Select GAGG:Ce 3+ as the first fluorescent particles, select YAG and Al2O3 as the coating layer. After proportionally weighing according to the metering ratio of the first fluorescent particles and the coating layer, mix them, then add appropriate dispersants, binders, and anhydrous ethanol. After mixing evenly, carry out grinding. After grinding, dry the system. During this process, the coating layer material coats on the outer surface of the first fluorescent particles. After drying, sieve it. The sieved powdery material is calcined at 800°C - 1000°C for at least 2 h to obtain the first fluorescent particles coated with the coating layer.
[0055] Select LuAG:Ce 3+As the second fluorescent particle, YAG and Al2O3 are selected as the coating layer. After weighing according to the stoichiometric ratio of the second fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the second fluorescent particle. After drying, sieving is carried out, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particle coated with the coating layer.
[0056] Prepare the fluorescent matrix. Weigh Lu3(Al,Ga)5O 12 :xCe 3+ , where x is the molar percentage of Ce substituting rare earth elements such as Y, Lu, and Gd. The raw materials are mixed and ground. The grinding can be carried out by ball milling. During the mixing process, an appropriate amount of sintering aid and dispersant are added. After grinding, the system is dried. After drying, sieving is carried out, and the sieved powdery material is calcined at 700 °C to 900 °C for at least 2 h to obtain the fluorescent matrix LuAGG:Ce 3+ .
[0057] Weigh the fluorescent matrix prepared above, and mix it with the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer according to a predetermined volume ratio. After mixing, sieving can be carried out again for standby.
[0058] The mixed fluorescent matrix, the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer are subjected to hot pressing, spark plasma sintering or isostatic pressing sintering under vacuum or protective atmosphere. The sintering temperature is 1500 °C to 1700 °C, the sintering pressure is 30 MPa to 100 MPa, and the heat preservation is 10 min - 10 h to obtain the fluorescent ceramic. After sintering is completed, the obtained fluorescent ceramic is subjected to annealing treatment. The annealing treatment can be carried out in air or oxygen atmosphere. The annealing temperature is 1000 °C to 1300 °C, and the heat preservation time is 2 h to 100 h.
[0059] Example 2
[0060] Select YAG:Ce 3+ as the first fluorescent particle, select YAG and Al2O3 as the coating layer. After weighing according to the stoichiometric ratio of the first fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the first fluorescent particle. After drying, sieving is carried out, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the first fluorescent particle coated with the coating layer.
[0061] Select LuAG:Ce 3+As the second fluorescent particle, YAG and Al2O3 are selected as the coating layer. After weighing according to the stoichiometric ratio of the second fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the second fluorescent particle. After drying, sieving is carried out, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particle coated with the coating layer.
[0062] Prepare the fluorescent matrix, weigh Lu3(Al,Ga)5O 12 :xCe 3+ , where x is the molar percentage of Ce substituting rare earth elements such as Y, Lu, Gd, etc. The raw materials are mixed and ground. The grinding can be carried out by ball milling. During the mixing process, an appropriate amount of sintering aid and dispersant are added. After grinding, the system is dried. After drying, sieving is carried out, and the sieved powdery material is calcined at 700 °C to 900 °C for at least 2 h to obtain the fluorescent matrix LuAGG:Ce 3+ .
[0063] Weigh the fluorescent matrix prepared above, and mix it with the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer according to a predetermined volume ratio. After mixing, sieving can be carried out again for standby.
[0064] The mixed fluorescent matrix, the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer are subjected to hot pressing or spark plasma sintering or isostatic pressing sintering under vacuum or protective atmosphere. The sintering temperature is 1500 °C to 1700 °C, the sintering pressure is 30 MPa to 100 MPa, and the heat preservation is 10 min - 10 h to obtain the fluorescent ceramic. After sintering is completed, the obtained fluorescent ceramic is subjected to annealing treatment. The annealing treatment can be carried out in air or oxygen atmosphere. The annealing temperature is 1000 °C to 1300 °C, and the heat preservation time is 2 h to 100 h.
[0065] Example 3
[0066] Select LuAGG:Ce 3+ as the first fluorescent particle, select Al2O3 as the coating layer. After weighing according to the stoichiometric ratio of the first fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the first fluorescent particle. After drying, sieving is carried out, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the first fluorescent particle coated with the coating layer.
[0067] Select YAG:Ce 3+As the second fluorescent particle, Al2O3 is selected as the coating layer. After weighing according to the stoichiometric ratio of the second fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the second fluorescent particle. After drying, it is sieved, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particle coated with the coating layer.
[0068] Prepare the fluorescent matrix. Weigh Gd3(Al,Ga)5O 12 :xCe 3+ , where x is the molar percentage of Ce substituting rare earth elements such as Y, Lu, Gd, etc. The raw materials are mixed and ground. The grinding can be carried out by ball milling. An appropriate amount of sintering aid and dispersant are added during the mixing process. After grinding, the system is dried. After drying, it is sieved, and the sieved powdery material is calcined at 700 °C to 900 °C for at least 2 h to obtain the fluorescent matrix GAGG:Ce 3+ .
[0069] Weigh the fluorescent matrix prepared above, and mix it with the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer according to a predetermined volume ratio. After mixing, it can be sieved again and set aside.
[0070] The mixed fluorescent matrix, the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer are subjected to hot pressing, spark plasma sintering or isostatic pressing sintering under vacuum or protective atmosphere. The sintering temperature is 1500 °C to 1700 °C, the sintering pressure is 30 MPa to 100 MPa, and the heat preservation is 10 min - 10 h to obtain the fluorescent ceramic. After sintering is completed, the obtained fluorescent ceramic is subjected to annealing treatment. The annealing treatment can be carried out in air or oxygen atmosphere. The annealing temperature is 1000 °C to 1300 °C, and the heat preservation time is 2 h to 100 h.
[0071] Example 4
[0072] Select YAG:Ce 3+ as the first fluorescent particle, select YAG and Al2O3 as the coating layer. After weighing according to the stoichiometric ratio of the first fluorescent particle and the coating layer and mixing, an appropriate amount of dispersant, binder and anhydrous ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the first fluorescent particle. After drying, it is sieved, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the first fluorescent particle coated with the coating layer.
[0073] Select GAGG:Ce 3+As the second fluorescent particle, YAG and Al2O3 are selected as the coating layer. After weighing according to the stoichiometric ratio of the second fluorescent particle and the coating layer and mixing them, an appropriate amount of dispersant, binder and absolute ethanol are added, and after mixing evenly, grinding is carried out. After grinding, the system is dried. During this process, the coating layer material is coated on the outer surface of the second fluorescent particle. After drying, it is sieved, and the sieved powdery material is calcined at 800 °C to 1000 °C for at least 2 h to obtain the second fluorescent particle coated with the coating layer.
[0074] Prepare the fluorescent matrix. Weigh Lu3(Al,Ga)5O 12 :xCe 3+ , where x is the molar percentage of Ce substituting rare earth elements such as Y, Lu, Gd, etc. The raw materials are mixed and ground. The grinding can be carried out by ball milling. An appropriate amount of sintering aid and dispersant are added during the mixing process. After grinding, the system is dried. After drying, it is sieved, and the sieved powdery material is calcined at 700 °C to 900 °C for at least 2 h to obtain the fluorescent matrix LuAGG:Ce 3+ .
[0075] Weigh the fluorescent matrix prepared above, and mix it with the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer according to a predetermined volume ratio. After mixing, it can be sieved again and set aside.
[0076] The mixed fluorescent matrix, the first fluorescent particle coated with the coating layer and the second fluorescent particle coated with the coating layer are subjected to hot pressing, spark plasma sintering or isostatic pressing sintering under vacuum or protective atmosphere. The sintering temperature is 1500 °C to 1700 °C, the sintering pressure is 30 MPa to 100 MPa, and the heat preservation is 10 min - 10 h to obtain the fluorescent ceramic. After sintering is completed, the obtained fluorescent ceramic is subjected to annealing treatment. The annealing treatment can be carried out in air or oxygen atmosphere. The annealing temperature is 1000 °C to 1300 °C, and the heat preservation time is 2 h to 100 h.
[0077] For the fluorescent ceramics prepared in the embodiments of the present application, on the one hand, it can realize the physical isolation of different luminescent ceramic phases, realize the independent luminescence of different ceramic phases, and obtain high-efficiency broadband fluorescence emission; on the other hand, the coating layer effectively reduces the pores around the first fluorescent particle and the second fluorescent particle, improves the density of the ceramic, can improve the thermal conductivity of the fluorescent ceramic, and can withstand high-power laser excitation; further, by changing the ratio of the three ceramic phases, the emission spectrum components of the fluorescent ceramic can be adjusted, and the color rendering index and color temperature of the white light source excited by high-power blue laser can be effectively regulated.
[0078] Example 5
[0079] Refer to Figure 2, this embodiment provides a light-emitting device 1, which includes a laser light source 20 and a fluorescent ceramic 10. The laser light source 20 emits excitation light to excite the fluorescent ceramic 10 to emit stimulated light. The fluorescent ceramic 10 can be any one of the foregoing embodiments, and the specific content can be referred to the relevant content of the foregoing embodiments.
[0080] Among them, the laser light source 20 can be, for example, a blue light source, such as a laser light source, an LED, or other light sources. In some other embodiments, the laser light source 20 can also be a light source of other colors, and this embodiment does not limit this.
[0081] The foregoing is only the preferred embodiment of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A fluorescent ceramic, characterized in that, Comprising: A fluorescent matrix; A first fluorescent particle filled within the fluorescent matrix; A second fluorescent particle filled within the fluorescent matrix; And A coating layer coating the outer surface of the first fluorescent particle and the outer surface of the second fluorescent particle; Wherein, the coating layer separates the fluorescent matrix, the first fluorescent particle and the second fluorescent particle from each other.
2. The fluorescent ceramic according to claim 1, wherein The fluorescent matrix, the first fluorescent particle and the second fluorescent particle respectively generate stimulated emission of different wavelength bands when excited.
3. The fluorescent ceramic according to claim 2, wherein The wavelength bands of the stimulated emission generated when the fluorescent matrix, the first fluorescent particle and the second fluorescent particle are excited are independently 490nm - 515nm or 515nm - 530nm or 535nm - 560nm.
4. The fluorescent ceramic according to claim 1, wherein, The fluorescent matrix is Ce 3+ doped garnet structure.
5. The fluorescent ceramic according to any one of claims 1-4, characterized in that, The coating layer comprises one or more of SiO2, MgO, Al2O3, YAG, or LuAG.
6. The fluorescent ceramic according to claim 5, wherein The proportion of the coating layer in the total volume of the fluorescent ceramic is 2% - 10%.
7. The fluorescent ceramic according to claim 5, wherein The thickness of the coating layer is 50nm - 200nm.
8. The fluorescent ceramic according to any one of claims 1-4, characterized in that, The total volume of the first fluorescent particle and the second fluorescent particle accounts for 10% - 80% of the total volume of the fluorescent ceramic.
9. The preparation method of the fluorescent ceramic according to any one of claims 1-7, characterized in that, Comprising: Coat the coating layer on the surface of the first fluorescent particle and the surface of the second fluorescent particle respectively, select a fluorescent matrix, mix it with the first fluorescent particle and the second fluorescent particle after coating the coating layer, and obtain the product after sintering.
10. The preparation method of the fluorescent ceramic according to claim 9, characterized in that, The coating the coating layer on the surface of the first fluorescent particle and the surface of the second fluorescent particle respectively comprises: Select the first fluorescent particle, add coating layer material, dispersant, binder and absolute ethanol, mix evenly, grind and dry, and calcine at 800°C - 1000°C for at least 2h to obtain the first fluorescent particle coated with the coating layer; Select the second fluorescent particle, add coating layer material, dispersant, binder and absolute ethanol, mix evenly, grind and dry, and calcine at 800°C - 1000°C for at least 2h to obtain the second fluorescent particle coated with the coating layer.
11. The method for preparing the fluorescent ceramic according to claim 9, wherein The sintering is carried out under the following conditions: Under vacuum or protective atmosphere, carry out hot pressing or spark plasma sintering or isostatic pressing sintering, the sintering temperature is 1500°C - 1700°C, the sintering pressure is 30MPa - 100MPa, and keep the temperature for 10min - 10h.
12. The method for preparing the fluorescent ceramic according to claim 11, wherein, The method further comprises a step of annealing treatment after sintering, and the annealing treatment is carried out in the following manner: Carry out in air or oxygen atmosphere, the annealing temperature is 1000°C - 1300°C, and the holding time is 2h - 100h.
13. A light-emitting device, comprising an excitation light source and the fluorescent ceramic according to any one of claims 1 - 8, wherein the excitation light source can emit excitation light to excite the fluorescent ceramic to emit stimulated emission.